Implementing child-friendly school principles in early childhood education: a field study on teachers’ practices and challenges - Santoso, Sandy Tegariyani Putri; Khusniyah, Syarifatul; Kamilah, Wardah Nuril (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
Early childhood education (ECE) is a crucial stage in children's holistic development, covering physical, cognitive, linguistic, social-emotional, and moral aspects. This article reviews the concept of Child-Friendly Schools (CFS) as a framework that places children's rights, protection, and participation as the main foundation of learning. National and international policies such as the Convention on the Rights of the Child and Indonesian instruments emphasize protection from violence and the fulfillment of children's rights, and UNICEF, through the concept of Child-Friendly Schools, has become the foundation for child-friendly practices in PAUD. Field studies conducted at three different PAUD institutions in Malang show that the implementation of CFS varies according to the local context, with the main supporting factors being the commitment of the school principal, ongoing teacher training, and parental involvement; the main obstacles include limited facilities, resources, and supervisory capacity. The findings indicate that the implementation of CFS improves a safe, inclusive, and supportive learning environment for positive parenting, while also increasing participation, well-being, and play-based learning. In real terms, the study suggests using more flexible and situation-based approaches, improving teachers' skills, and building strong connections between schools, families, and communities to better support the long-term success of CFS.